2023
DOI: 10.1109/jstars.2023.3238188
|View full text |Cite
|
Sign up to set email alerts
|

Combining Luojia1-01 Nighttime Light and Points-of-Interest Data for Fine Mapping of Population Spatialization Based on the Zonal Classification Method

Abstract: Fine-scale population spatial distribution plays an important role in urban microcosmic research, influencing infrastructure placement, emergency evacuation management, business decisions, and urban planning. In the past, nighttime light (NTL) data were generally used to map the spatial distribution of the population at a large scale because of their low spatial resolution. The new generation of Luojia1-01 NTL data can be used for fine-scale social and economic analysis with its high spatial resolution and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Consequently, techniques utilizing remote sensing data from nighttime lights [8][9][10][11][12] and land use classifications [13][14][15][16] to spatialize population information have gained traction. Moreover, the advent of computational artificial intelligence has led to the application of geographically weighted regression [17][18][19][20][21] and machine learning methods [22,23] for producing fine-grained visual representations of population distribution using both traditional geographic and geographical big data [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, techniques utilizing remote sensing data from nighttime lights [8][9][10][11][12] and land use classifications [13][14][15][16] to spatialize population information have gained traction. Moreover, the advent of computational artificial intelligence has led to the application of geographically weighted regression [17][18][19][20][21] and machine learning methods [22,23] for producing fine-grained visual representations of population distribution using both traditional geographic and geographical big data [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, spatial big data have been gradually considered to overcome the limitations of nighttime light data. In particular, a number of previous studies have shown that POIs can effectively reflect socio-economic activities and urban vitality [51,55], while housing price is also an important indicator of economic and residential conditions [56,57]. Therefore, it is feasible to combine these various different data sources for fine-scale poverty estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Timely and reliable gridded population data are highly desired to meet this demand, especially in countries experiencing rapid urbanization and internal migration like China. In China, informed decision-making and sustainable urban development greatly depend on timely and accurate gridded population distribution data (Chen et al, 2020b;Cheng et al, 2020;Guo et al, 2023;Tu et al, 2022). The Seventh National Population Census of China, conducted in 2020, presents a valuable opportunity to produce the required up-to-date and reliable gridded population data.…”
mentioning
confidence: 99%